Interleukin-6: back to the future - Kishimoto, Tadamitsu (Henry Stewart Talks, 2011)
IL-6 is a pleiotropic proinflammatory cytokine, Its overproduction is involved in inflammatory autoimmune diseases including rheumatoid arthritis, Blocking of IL-6 signals by anti-IL6 receptor antibody (Tocilizumab) shows therapeutic effect on various autoimmune diseases, Tocilizumab exerts its effect by inhibiting the induction of a helper T cell subset (TH17), Aryl-hydrocarbon receptor (Ahr) is one of the essential molecule for the IL-6 mediated induction of TH17 cells